Ocular manifestations in fetal alcohol syndrome. Issue 9 (September 1991) - Chan, T; Bowell, R; O'Keefe, M; Lanigan, B
Abstract : Eight children with the fetal alcohol syndrome are described with ocular anomalies. They all had a strong history of maternal alcohol abuse throughout pregnancy, especially in the first trimester. All the children had eye abnormalities. These included external eye lesions, Peters' anomaly, lens opacification, ocular motility disorders, and optic nerve hypoplasia.